Financial factors in economic fluctuations - Lawrence Christiano; Massimo Rostagno; Roberto Motto (European Central Bank (ECB), 2010)
We augment a standard monetary DSGE model to include a banking sector and financial markets. We fit the model to Euro Area and US data. We find that agency problems in financial contracts, liquidity constraints facing banks and shocks that alter the perception of market risk and hit financial intermediation — `financial factors' in short — are prime determinants of economic fluctuations. They have been critical triggers and propagators in the recent financial crisis. Financial intermediation turns an otherwise diversifiable source of idiosyncratic economic uncertainty, the `risk shock', into a systemic force.
Keywords: E3; E22; E44; E51; E52; E58; C11; G1; G21; G3; 330; Bayesian estimation; DSGE model; Financial Frictions; Financial shocks; Funding channel; Lending channel; Dynamisches Gleichgewicht; Bank; Finanzmarkt; Liquiditätsbeschränkung; Schock; Marktrisiko; Geldpolitik; Geldpolitische Transmission; Eurozone; EU-Staaten; USA